Kegiatan Sosialisasi Telkom Solution Business Partner (TSBP) Dalam Meningkatkan Sikap Karyawan Menangani Kasus Pelanggan Telkom Solution - Dian Dwiyane (KOM & REALITAS SOSIAL, 2011)
PT. Telekomunikasi Indonesia Tbk. is the largest company engaged in communications services, to full fill the needs of telecommunications in a growing business world. PT. Telekomunikasi Indonesia Tbk. (Telkom) launched